Pengaruh Kualitas Pelayanan Dan Ketepatan Waktu Terhadap Kepercayaan Pelanggan J&T Express Km.8 Atas Tanjungpinang - Husnul Khatimah; Kamaruzaman (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2025)
This research is based on an increase in the number of customers and an increase in complaints related to service quality and delivery timeliness. This prompted the researcher to analyze the influence of service quality and punctuality on customer trust at J&T Express Km.8 over Tanjungpinang. The type of research used is quantitative research. The population is 97 respondents. The research sample used a non-probability sampling technique. Data collection was carried out by questionnaire method distributed to customers. The analysis technique uses multiple linear regression. Data that have qualified for analysis are processed using the help of the SPPS 25 program. The results of this study show that the variables of service quality and punctuality have a positive and significant effect on customer trust, so that the hypothesis can be accepted, as well as the results of the coefficient test obtained (R Square), 59.4% which means that the ability of independent validity is strong to explain dependent variables and the remaining 40.6% can be explained by other variables outside of the research variable.